2017
DOI: 10.1080/09168451.2017.1387048
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PVT1 predicts prognosis and regulates tumor growth in prostate cancer

Abstract: Long non-coding RNA (lncRNA) plasmacytoma variant translocation 1(PVT1) was aberrantly expressed in various cancers and is associated with tumor prognosis. Here, we aim to investigate its function in prostate cancer. Small interfering RNA against PVT1 was transfected into prostate cancer cell lines and cell growth and apoptosis were analyzed. Our results showed that PVT1 was overexpressed in prostate cancer tissues and cells. Higher levels of PVT1 indicated poorer overall survival and disease-free survival. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 30 publications
6
62
0
4
Order By: Relevance
“…2). Concordantly, Yang et al [10] reported recently that higher levels of this lncRNa were associated with poorer overall survival and disease-free survival. Moreover, they showed that PVT1 knockdown by small interfering RNA transfection significantly inhibited PCa growth in vivo and in vitro and promoted cell apoptosis, suggesting that PVT1 played an oncogenic role in PCa.…”
supporting
confidence: 54%
“…2). Concordantly, Yang et al [10] reported recently that higher levels of this lncRNa were associated with poorer overall survival and disease-free survival. Moreover, they showed that PVT1 knockdown by small interfering RNA transfection significantly inhibited PCa growth in vivo and in vitro and promoted cell apoptosis, suggesting that PVT1 played an oncogenic role in PCa.…”
supporting
confidence: 54%
“…Downregulation of expression of the long noncoding RNA (lncRNA) from PVT1 inhibits proliferation and migration by regulating p38 expression in PCa [19]. Increasing evidence has shown the important role of lncRNAs in many different biological processes [23][24][25][26][27][28][29][30][31]. PVT1 itself has been implicated in cell proliferation, apoptosis, lymph node invasion, metastasis, and tumor prognosis [23].…”
Section: Discussionmentioning
confidence: 99%
“…A high PVT1 expression level in patients with prostate cancer has been shown to be associated with low overall survival. PVT1 expression is significantly correlated with tumor stage and can promote tumor cell proliferation, invasion, and metastasis in prostate cancer [128,144]. The expression of PVT1 in ovarian cancer tissues is higher than that in normal ovarian tissue and is related to the advanced stage of ovarian cancer and lower overall survival.…”
Section: Perspectivesmentioning
confidence: 99%
“…PVT1 can downregulate the expression of caspase-9, caspase-7, and poly ADP-ribose polymerase, thereby inhibiting apoptosis and ultimately leading to radiation tolerance [14]. Studies have also shown that PVT1 can downregulate the expression of caspase-3 to inhibit apoptosis [143,144]. Therefore, PVT1 may participates in the downstream apoptosis-related signaling pathway of c-Myc by affecting MDM, caspase-9, and caspase-3 ( Fig.…”
Section: Pvt1 Participates In the Downstream Apoptosis-related Signalmentioning
confidence: 99%